Rethinking strategy on developing students’ levels of geometric thinking in Sokoto state, Nigeria - Muhammad Nasiru Hassan; Abdul Halim Abdullah; Norulhuda Ismail (International Journal of Evaluation and Research in Education (IJERE), 2023)
Geometric thinking skills remained a topical issue in mathematics education. The purpose of this research is to investigate the van Hiele levels of geometric thinking skills of the students in Sokoto state to provide a clear picture of the students’ levels for the appropriate development of learning activities, and better understanding. The study involves three mathematics teachers and 200 students (100 students each of basic and senior secondary school students). The samples of the teachers were purposely selected and students were randomly selected. There were two instruments used in the study; interviews for the mathematics teachers while a van Hiele test for geometric thinking was adopted to collect data for the students’ van Hiele levels of thinking. Thematic analysis (for teachers’ interview), descriptive, and Mann-Whitney U test for the analysis of students’ van Hiele levels of thinking was used. The result shows that all the teachers indicate that the traditional approach is the dominant method used in teaching and learning and that students in the state lack basic skills in school geometry. Also, the result indicated that the majority of students sample among Basic and Senior secondary schools in Sokoto state were operating at level 0 respectively. Furthermore, a significant difference between the two independent groups was found in favor of senior secondary school students. It is hoped that in the future, educational institutions could use the present research as a guide for the development and design of modules, learning activities based on the van Hiele levels to bridge the gap in the state.